Finite Element Analysis of Uncemented Total Hip Replacement: the Effect of Bone-Implant Interface - Faiqa Ismail, Nur; Shuib, Solehuddin; Azman Yahaya, Muhd; Zafir Romli, Ahmad; Ahmed Shokri, Amran (International Journal of Engineering and Technology, 2018)
Most uncemented total hip replacements (THR) rely on press-fit for the initial stability and thus lead to the secondary fixation which is biological fixation. Choosing the accurate interference fit may have a great effect on implant stability and implant loosening prevention. Implant loosening is the most reported problem where it leads the increasing of micromotion at the bone-implant interface due to insufficient primary fixation. By having sufficient stability or fixation after surgery, minimal relative motion between the prosthesis and bone interfaces allows osseointegration to occur. Therefore, it will provide a strong prosthesis-to-bone biological attachment. The aim of this study was to evaluate the effect of bone-implant interface for uncemented hip implant. In this study, a three-dimensional model of hip implant was designed and analysed by using commercial Finite Element Software namely, ANSYS WORKBENCH V15 software in order to investigate the bone-implant interface effect using the chosen implant design. The value of interference fit (Î´= 0.01, 0.05, 0.10 and 0.50 mm) and coefficient of friction (Î´= 0.15, 0.40 and 1.00) were used to simulate the bone-implant interface. It was found that the interference fit of 0.50 mm was sufficient to achieve the primary fixation and also the best fitting; thus, the implant loosening can be minimized. The interference fit of 0.50 mm was the minimal value to achieve fixation, while the coefficient of friction did not affect the bone-implant interface.Â